'BRIGANDS' AND 'TYRANTS' IN JOSEPHUS' BELLVM JVDAICVM. (December 2021) - Ben-Yishai, Steven
Abstract: This article argues against the long-enduring practice of Josephan scholarship to treat the terms τύραννος ('tyrant') and λῃστής ('brigand') as a collocation, or as undistinguished terms of invective employed by Josephus against various Jewish antagonists in his Bellum Judaicum (= BJ ). Towards this aim, the article first examines the frequency in which these two terms appear together throughout the text of the BJ, before turning to a critical examination of particular passages that feature the terms, in order to prove that they are, in fact, not used as undistinguished terms of invective but as terms pertaining to two distinct classes of people: renegade aristocrats vying with their peers for absolute power (the 'tyrants') and their gangs of foot soldiers comprising men from the lower classes (the 'brigands'). The article concludes that Josephus used these terms in this manner in order to convey to his readership, which largely consisted of Roman aristocrats, that the ringleaders of the Judaean revolt which raged between a.d. 66–73 were akin to renegades who periodically wreaked havoc on Rome's own aristocracy, often with devastating consequences for class and country alike.